2012
DOI: 10.1128/jvi.01498-12
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Chimpanzees, but Not Bonobos, Represent a Simian Immunodeficiency Virus Reservoir

Abstract: Chimpanzees in west central Africa ( Pan troglodytes troglodytes ) are endemically infected with simian immunodeficiency viruses (SIVcpz Ptt ) that have crossed the species barrier to humans and gorillas on at least five occasions, generating pandemic and nonpandemic forms of human immunodeficiency virus type 1 (HIV-1) as well as gorilla SIV (SIVgor). Chimpanzees in east Africa ( Pan troglodytes schweinfurthii ) are also infected with SIVc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 79 publications
(165 reference statements)
1
88
2
Order By: Relevance
“…1); yet, we identified SIVgor-positive gorillas only at six sites, all located in southern Cameroon. Overall, we found fewer than 2% of western lowland gorillas to be infected with SIVgor, which is much lower than the estimates of SIVcpz infection rates for central (6%) or eastern (13%) chimpanzees (4,6,16). Although it is possible that some fecal samples were too degraded to yield positive results, this possibility alone cannot explain the low SIVgor detection rates in western gorillas or the lack of infection in eastern gorillas.…”
Section: Sivgor In Gorillas Is Less Common and Widespread Than Sivcpz Incontrasting
confidence: 39%
See 3 more Smart Citations
“…1); yet, we identified SIVgor-positive gorillas only at six sites, all located in southern Cameroon. Overall, we found fewer than 2% of western lowland gorillas to be infected with SIVgor, which is much lower than the estimates of SIVcpz infection rates for central (6%) or eastern (13%) chimpanzees (4,6,16). Although it is possible that some fecal samples were too degraded to yield positive results, this possibility alone cannot explain the low SIVgor detection rates in western gorillas or the lack of infection in eastern gorillas.…”
Section: Sivgor In Gorillas Is Less Common and Widespread Than Sivcpz Incontrasting
confidence: 39%
“…Molecular epidemiological studies of SIVcpz have shown that these viruses exhibit phylogeographic clustering, apparently largely due to major rivers and other barriers that limit the migration of wild chimpanzees (4)(5)(6). This clustering has allowed us to pinpoint the probable geographic origins of two of the human virus clades (4).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…We first tested whether divergent strains of SIVcpz can infect hu-BLT mice. We selected 4 phylogenetically divergent SIVcpz strains to represent the inferred ancestral viruses of pandemic HIV-1 group M (SIVcpzMB897) and nonpandemic HIV-1 group N (SIVcpzEK505) (6,26), as well as SIVcpzMT145 (6) and SIVcpzBF1167 (27), whose viral lineages have not been found in humans (4,8). We included HIV-1 SUMA , a (Table 1), from which each hu-BLT mouse was inoculated intraperitoneally (i.p.)…”
Section: Resultsmentioning
confidence: 99%